DETERMINANT DIGITAL LEARNING BASED INCLUSIVE SCHOOL - basit, abdul; Puspitarini, Renny Candradewi (RONTAL: Jurnal Keilmuan Pancasila dan Kewarganegaraan, 2020)
The problems of research are: a) the lack of teacher and student readiness to learn, b) the lack of Wi-Fi speed, c) the level of dependent on school operator, and d) the lack of learning methodology. Based on those problems, this research aims to to strengthen the learning outcomes expected by PPKn (civic study teacher) subject teachers in providing excellent service not only in learning process but also activities outside the classroom at inclusive schools. Research informants involved in this research are inclusive students (with special needs), teachers with the initials AH, S, school principals of the initials YES, 3 inclusive mentor teachers with initials of RAA, TM and BH as well as SRH / school principals as primary sources /key informants. Secondary informants also involved researchers such as the community, school committees, school supervisors, counseling teachers with the initials JK. This research approach uses qualitative research in the form of analytical descriptive. The process of collecting data uses observation, interviews and documentation studies. The result is there is effectiveness of education and training followed by teachers. Students' learning motivation increases compared to using classical methods such as lectures and is monotonous and mundane. This is caused by the efforts of teachers in utilizing IT properly. Teachers use IT learning, not only in the I-Spring Suite and Edmodo applications owned by the school, but also compile questions through the Google form so that synchronization of questions is no longer dependent and waiting for school operators. Teachers can operate on their own according to school rules and regulations. However, inclusion students are treated differently and given different questions / questions. This also relates to the 2013 curriculum that has been used by teachers with necessary modification, especially for inclusive students